Tối ưu hóa việc mở rộng quy mô và khai thác một hệ thống - Lam, Lê Xuân; Quỳ, Tống Đình (Journal of Computer Science and Cybernetics, 2016)
This paper presents a method to construct an optimal control problem of a system connected with scale expand and exploit as control a random process.